Competitive State Anxiety, motivation and sports performance of the female soccer team of the Fundación Universitaria Católica Lumen Gentium, in Cali, Colombia - Biscué Viáfara, Christian David (SATHIRI, 2022)
The objective of the research was to explore the effect of motivation and Competitive State Anxiety (CSA) on the sports performance of eight women belonging to the representative futsal team of the Fundación Universitaria Católica Lumen Gentium (Unicatólica) located in Cali, Colombia. It was interpreted, from the postulates of sport psychology, the motivation and anxiety state in a competitive situation. CSA was characterized in female soccer players using the Competitive State Anxiety Inventory in its revised version II (CSAI-2R), registering a minimum level of 7 and a maximum of 23 in somatic anxiety, (Very low-Medium), the cognitive anxiety scored between 5 and 15 (Very Low-Low); The level of motivation was established from the Sports Motivation Scale (SMS) between 75 and 85 (High-Very high) in intrinsic motivation, from 24 to 82 (Low-Very high) in extrinsic motivation; The effects on the team's sports performance were analyzed using a Sports Performance Record Sheet. The methodology used was exploratory, proposing to determine the characteristics of the athletes selected by a non-probabilistic sampling with a non-experimental and descriptive type of study from a hypothetical deductive design. it was found that motivation and C.S.A. influence sports performance, it could be concluded that athletes build skills to obtain positive results in the field, such as maintaining the motivational focus under the pressure of competition and taking advantage of individual skills to achieve optimal team performance.
Keywords: Competitive State Anxiety; motivation; sports psychology; sports performance; women´s soccer